2019
DOI: 10.1136/bmjopen-2018-028735
|View full text |Cite
|
Sign up to set email alerts
|

Research priorities and potential methodologies to inform care in subsequent pregnancies following stillbirth: a web-based survey of healthcare professionals, researchers and advocates

Abstract: ObjectivesTo identify research priorities and explore potential methodologies to inform care in subsequent pregnancies following a stillbirth.DesignWeb-based survey by invitation.ParticipantsMultidisciplinary panel of 79 individuals involved in stillbirth research, clinical practice and/or advocacy from the international stillbirth research community (response rate=64%).Outcome measuresImportance of 16 candidate research topics and perceived utility and appropriateness of randomised controlled trial (RCT) meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 50 publications
0
23
0
Order By: Relevance
“…Table 2 shows the particular social media strategies used to enhance knowledge user engagement in research priority-setting exercises grouped by platform. Of studies using email as their primary social media platform [ 12 , 16 , 17 , 19 , 23 , 24 , 27 , 29 , 30 , 33 ] study teams emailed messages with embedded research prioritization survey links (including to researchers’ existing mailing lists) and integrated tell a friend tool in emails to prompt recipients to invite colleagues to participate. Facebook-specific methods to engage stakeholders included embedding survey links within Facebook posts, using the platform’s boosting feature (ie, paid advertisements), and hiring a Facebook advertising specialist.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2 shows the particular social media strategies used to enhance knowledge user engagement in research priority-setting exercises grouped by platform. Of studies using email as their primary social media platform [ 12 , 16 , 17 , 19 , 23 , 24 , 27 , 29 , 30 , 33 ] study teams emailed messages with embedded research prioritization survey links (including to researchers’ existing mailing lists) and integrated tell a friend tool in emails to prompt recipients to invite colleagues to participate. Facebook-specific methods to engage stakeholders included embedding survey links within Facebook posts, using the platform’s boosting feature (ie, paid advertisements), and hiring a Facebook advertising specialist.…”
Section: Resultsmentioning
confidence: 99%
“…The direct effect of social media campaigns in securing stakeholder participation in research priority-setting was assessed as the (1) number of survey responses [ 12 , 14 , 15 , 20 , 33 ], (2) number of survey responses within a set period [ 14 , 15 , 20 , 33 ], (3) proportion of surveys fully completed [ 21 ], and (4) number of visits to external survey administration sites [ 14 , 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…A priority setting exercise of 79 professionals involved in stillbirth research reported that targeted interventions for pregnancy after loss and specialist clinical services such as PALCs were identified as urgent and important by 79% and 73% of respondents respectively. Importantly, fewer 50% of respondents of respondents felt that randomised controlled studies were the best way to evaluate psychological interventions, or were likely to be feasible [ 29 ]. Nevertheless, models of care in pregnancy after loss need to be developed and evaluated in order that effective care can be delivered to women and their families in these pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…Provision of specialist care in a dedicated clinical service was viewed favourably, but comparative studies are required to determine whether this model is superior to routine high-risk care and to identify which components of the dedicated service are valued. A recent prioritisation study found 73% of respondents indicated that this was an urgent and important research question to be addressed [36]. Further studies are also needed to understand partners' and other family member's experiences of pregnancy/ies after stillbirth to appreciate which aspects of care and support are bene cial in a future pregnancy.…”
Section: Discussionmentioning
confidence: 99%